Science dictionary - Simon, Seymour (New York : HarperCollins, 1994)
A dictionary of useful scientific terms covering many branches of sciences, biographies of 85 scientists, and many informative tables and charts.
School Library Journal.
Wilson's Children.
Wilson's Junior High School.
8.5
3-6
4-6
Keywords: Science -- Dictionaries, Juvenile; Science -- Dictionaries; Science -- Dictionaries